2022
DOI: 10.3390/su14126986
|View full text |Cite
|
Sign up to set email alerts
|

ATS-STEM: Global Teaching Methodology to Improve Competences of Secondary Education Students

Abstract: Previous studies agree on the benefits of improving the relevant competences in students by applying globalized learning methodologies and projects in the STEM fields (Science, Technology, Engineering and Mathematics). However, few studies have focused on whether including other subjects in Humanities, Arts and Social Sciences (HASS) in these projects improves high school students’ perceptions on improvement in these skills. The objective of this work was to study the effect of participation in interdisciplina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
(71 reference statements)
0
5
2
Order By: Relevance
“…Thus, we predicted that students would demonstrate greater learning motivation after the courses, especially in the experimental group (Hypothesis 2). Fernández-Morante et al (2022) confirmed the effects of incorporating various art strategies into STEM learning on a large number of learners’ STEM efficacy. Hence, we predicted that diverse students would demonstrate better STEAM efficacy after the completion of the courses, especially in the experimental group (Hypothesis 3).…”
Section: Theoretical Frameworkmentioning
confidence: 53%
See 4 more Smart Citations
“…Thus, we predicted that students would demonstrate greater learning motivation after the courses, especially in the experimental group (Hypothesis 2). Fernández-Morante et al (2022) confirmed the effects of incorporating various art strategies into STEM learning on a large number of learners’ STEM efficacy. Hence, we predicted that diverse students would demonstrate better STEAM efficacy after the completion of the courses, especially in the experimental group (Hypothesis 3).…”
Section: Theoretical Frameworkmentioning
confidence: 53%
“…Several studies have incorporated arts into STEM courses and examined their effects on student performance (Arce et al, 2022; Chen et al, 2022; Cheng et al, 2022; Erol et al, 2023; Fernández-Morante et al, 2022; Ju et al, 2022; Khamhaengpol et al, 2022; Timotheou & Ioannou, 2021; Weng et al, 2023). In these studies, the arts were not merely used as decoration; rather, they were presented through strategies, including arts/esthetic, contextual understanding, creativity, and combinations of these.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations